2016
DOI: 10.1038/cddis.2016.303
|View full text |Cite
|
Sign up to set email alerts
|

Circulating histones are major mediators of systemic inflammation and cellular injury in patients with acute liver failure

Abstract: Acute liver failure (ALF) is a life-threatening systemic disorder. Here we investigated the impact of circulating histones, recently identified inflammatory mediators, on systemic inflammation and liver injury in murine models and patients with ALF. We analyzed histone levels in blood samples from 62 patients with ALF, 60 patients with chronic liver disease, and 30 healthy volunteers. We incubated patients' sera with human L02 hepatocytes and monocytic U937 cells to assess cellular damage and cytokine producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 35 publications
(48 reference statements)
3
55
1
1
Order By: Relevance
“…Histones have been shown to induce thrombocytopenia in mice, 34 and have been implicated in thrombocytopenia in patients admitted to intensive care. 35 As levels of circulating histones are slightly elevated in patients with cirrhosis, and substantially elevated in patients with acute liver failure, 36 the role of histones in the thrombocytopenia of liver disease should be further explored. Next to their thrombocytopenia, patients with cirrhosis may have a prolonged skin bleeding time indicative of platelet defects.…”
Section: The Hemostatic Status In Patients With Cirrhosismentioning
confidence: 99%
“…Histones have been shown to induce thrombocytopenia in mice, 34 and have been implicated in thrombocytopenia in patients admitted to intensive care. 35 As levels of circulating histones are slightly elevated in patients with cirrhosis, and substantially elevated in patients with acute liver failure, 36 the role of histones in the thrombocytopenia of liver disease should be further explored. Next to their thrombocytopenia, patients with cirrhosis may have a prolonged skin bleeding time indicative of platelet defects.…”
Section: The Hemostatic Status In Patients With Cirrhosismentioning
confidence: 99%
“…It is suggested that histone mediates cell death and inflammation by binding to Toll‐like receptors (eg, TLR‐4 and TLR‐9) 14. Activation of TLRs may trigger the downward cascade including the inflammasome to activate pyroptosis and produce proinflammatory cytokines, exacerbating the injury and causing a systemic response 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…14 Activation of TLRs may trigger the downward cascade including the inflammasome to activate pyroptosis and produce proinflammatory cytokines, exacerbating the injury and causing a systemic response. 15,16 Pyroptosis is a lytic type of cell death and a form of regulated necrosis that is inherently associated with inflammation and distinguished from other forms of cell death by the associated secretion of interleukin (IL)-1β after caspase-1 activation. The cellular processes that occur during pyroptosis include nuclear condensation, DNA damage, cell swelling, and, finally, cell lysis, with the subsequent release of IL-1β and are reliant on intracellular sensors of bacterial products and formation of the inflammasome.…”
Section: Introductionmentioning
confidence: 99%
“…LA-4,94 94 mouse type II pneumocytes, 98 L02 hepatocytes,100 CHO-K1,101 CHO-A745101 Calcium influx, cytokine (IL-1β, IL-6, IL-10, TNFa) production (A549, BEAS-2B, LA-4) and cell death (PI/ LDH; all cell types)…”
mentioning
confidence: 99%